Benefits of energy related building renovation in residents comfort and well-being – Vila d’Este case study - Almeida, Manuela Guedes de (2016)
The relevance of the building sector in the global energy use as well as in the global carbon emissions makes the improvement of the overall energy performance of existing buildings an important part of the actions to mitigate climate changes. Regardless of this potential, large-scale building renovation has been found hard to trigger, with present standards mainly focused on new buildings, not responding effectively to the technical, functional and economic constraints of the existing ones. One of the common problems in the assessment of building renovation scenarios is that only energy savings and costs are normally considered, despite the fact that the investment on energy efficiency yield several benefits beyond the value of saved energy (the so-called co-benefits). To demonstrate and highlight the relevance of co-benefits achieved in the renovation process, a Portuguese neighbourhood with nearly 17.000 inhabitants that has been recently renovated is analysed in search for evidences of the existence of these co-benefits and their relevance. Indoor temperature, humidity and noise insulation were monitored and a survey to the residents was carried out. Results clear indicate the achievement of co-benefits at the building level such as increased user comfort and reduced problems with building physics (mould and water infiltrations), but also the elimination of the feeling of gentrification by outside people to the neighbourhood. The analysis demonstrates that the decision-making process canâ t only be based on investment costs and energy savings, being necessary that owners, investors, promoters, but also policy makers adapt their reasoning to include these additional benefits.